2017
DOI: 10.3389/fphys.2017.01006
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism rs1761667 in the CD36 Gene Is Associated to Changes in Fatty Acid Metabolism and Circulating Endocannabinoid Levels Distinctively in Normal Weight and Obese Subjects

Abstract: The multifunctional CD36 scavenger receptor facilitates fatty acid (FA) uptake and oxidation and it has been involved in the pathophysiology related to dysfunctional FA metabolism. The common variant in the CD36 gene, rs1761667 (A/G), whose allele A is characterized by a reduced protein expression, has been associated with taste sensitivity to and preference for fat. We therefore aimed at evaluating whether the CD36 polymorphism may influence fatty acid metabolism and endocannabinoid biosynthesis in normal wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 68 publications
1
34
1
Order By: Relevance
“…Patients also demonstrated signs of cardiomyopathy, probably due to impaired uptake of long-chain fatty acids essential to maintaining normal heart function. Population studies have also identified several CD36 polymorphisms linked to increased risk of metabolic syndrome, acute myocardial infarction and type 2 diabetes [ 81 , 94 , 95 , 96 , 97 , 98 ], which might support their determination in the context of personalized therapeutic strategies. In particular, polymorphisms found to impair LDL-binding domain of CD36 were correlated with increased cardiovascular risk factors and unstable plaque formation.…”
Section: Scavenger Receptor Cd36 a Target Of Hexarelinmentioning
confidence: 99%
“…Patients also demonstrated signs of cardiomyopathy, probably due to impaired uptake of long-chain fatty acids essential to maintaining normal heart function. Population studies have also identified several CD36 polymorphisms linked to increased risk of metabolic syndrome, acute myocardial infarction and type 2 diabetes [ 81 , 94 , 95 , 96 , 97 , 98 ], which might support their determination in the context of personalized therapeutic strategies. In particular, polymorphisms found to impair LDL-binding domain of CD36 were correlated with increased cardiovascular risk factors and unstable plaque formation.…”
Section: Scavenger Receptor Cd36 a Target Of Hexarelinmentioning
confidence: 99%
“…In particular, the substitution of A for G in the rs1761667 single nucleotide polymorphism (SNP) has been shown to decrease expression of this protein (Love‐Gregory et al., ) and associate with a reduced ability to detect fatty acids orally (Melis, Sollai, Muroni, Crnjar, & Barbarossa, ; Mrizak et al., ; Pepino, Love‐Gregory, Klein, & Abumrad, ). Recent evidence also suggests that this polymorphism is differentially associated with plasma lipid markers, such as endocannabinoid levels, and body composition in lean and obese individuals (Melis et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that variations in fat perception and obesity are associated with common variants in CD36 gene [ 8 , 16 , 17 ]. In particular, several data showed that the polymorphism rs176166 (A/G), whose allele A is characterized by a decreased protein expression, could explain individual variations in fat orosensory perception [ 18 20 ], as well as the different metabolic pattern found between lean and obese subjects [ 21 ].…”
Section: Introductionmentioning
confidence: 99%